Geography's Place in Higher Education in Singapore - Kong, Lily (Institutional Knowledge at Singapore Management University, 2007)
Unlike the other papers in this symposium, which deal with countries where there are large numbers of universities, and comparison can be made over time and across space of geography's place in higher education, this paper focuses on a country that was for a long time described as a 'one-university town': Singapore. What interesting story call there be when geography's presence in higher education is so circumscribed? In this paper, the author illustrates how geography's,fate in higher education in Singapore is closely bound up with developments in other parts of the world, not unlike the way in which the country's destiny is integrally linked with global economic, social and political developments. Yet, geography in higher education in Singapore has also managed to maintain a trajectory of growth and significance, problems in many other places notwithstanding. It has also maintained all identity in uenced by developments elsewhere, yet simultaneously unique. In what follows, the author outlines the presence and complexion of geography in Singapore's higher education landscape, and the interlocking relationships with pre-tertiary geography education, international flows, internal university relations, and geography in the public imagination, all of which shape the character of geography in Singapore's higher education.